Liberia : First Review of Performance Under the Staff-Monitored Program. (IMF Staff Country Reports; Country Report ;, 2006)
Economic developments are broadly in line with the original program projections for the year. The authorities have made considerable progress in implementing the IMF staff-monitored program (SMP), and the program is broadly on track. Substantial efforts to improve revenue administration raised revenue by 18 percent in February-June 2006, compared with the corresponding period in 2005. The financial position of the Central Bank of Liberia (CBL) also improved. Serious capacity constraints also affect the ability of the authorities to achieve all of the objectives.